'On the brink of a fever stricken swamp': Culturally modified trees and land-people relationships at the Lower Laura (Boralga) Native Mounted Police camp, Cape York Peninsula. Issue 1 (15th July 2020) - Cole, Noelene; Wallis, Lynley A.; Burke, Heather; Barker, Bryce; ,
Abstract: The archaeological record of Lower Laura (aka Boralga) Native Mounted Police camp, a longstanding base for Queensland' s frontier war in Cape York Peninsula, includes a diverse assemblage of culturally modified Erythophleum chlorastychys (Cooktown ironwood) trees. Analysis of cultural scar attributes and tool marks – which were found to be variously associated with Aboriginal stone tools, tomahawks of different types, and long handled axes – reveals a scenario of nineteenth century land use and technology that transcends the pre-conflict era of Aboriginal clan estates. As well as reflecting traditional patterns of Aboriginal tenure of prime waterfront land, the assemblage reveals innovations that occurred in Aboriginal technology in the lead-up to war. However, an unusual style of cultural scar cut using long handled axes appears to signal transformations in demography and land use following Native Mounted Police occupation. By integrating historical, oral history, spatial, typological, and botanical data this study provides evidence of demographic and environmental changes set in train by the gold-rush invasion. It also highlights the complexities of documenting Cooktown ironwood trees of advanced age and their fragile, deteriorating cultural modifications.